Backbone of the Syrian revolt: Inclusion of rural Sunnis key for international efforts to end conflict - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2015)
Syria's descent into civil war following the military crackdown on the peaceful protest movement in 2011 has thrust the country's rural Sunnis to the forefront. As the civil war dragged on, the countryside became the recruiting reservoir for rival jihadist factions after the demise of the Arab- and Western-backed Free Syrian Army. Divisions within the Syrian political opposition based in Istanbul also delayed the formation of a provisional government. Foreseeing a strengthened Iran, some of these jihadists have put out feelers to the West. Whether and how they could contribute to conflict resolution needs to be explored. Yet on the ground, the jihadists have largely failed at administering the areas they have captured. That evolving disparity - disenchantment with the militants and lack of appetite for a return to Assad's rule - offers an opportunity to reactivate the dormant opposition government, which Germany initially backed but then let drift. (SWP Comments)
Keywords: 320